Odpowiedzi

Najlepsza Odpowiedź!
2009-12-02T16:19:29+01:00
H₂SO₄ = 2*mH + mS + 4 *mO = 2*1u + 32u + 4*16u = 2u+32u + 64u= 98u

32u/98u * 100% = ok 32,65 %

H₂SO₃ = 2*mH + mS + 3 *mO = 2*1u + 32u + 3*16u = 2u+32u + 48u=82u

32u/82u * 100% = ok. 39,02 %

W kwasie siarkowym (IV) jest więcej siarki niż w kwasie siarkowym (VI) o ok 6%
2009-12-02T18:08:22+01:00
H₂SO₃ = mH ×2 + mS + mO× 3 = 1×2 + 32 + 16× 3 = 2+32+48 = 82u

Siarka :
82u - 100%
32u - x
82x - 3200/:82
x - 39.02%

H₂SO₄ = mH ×2 + mS + mO× 4 = 1×2 + 32 + 16×4 = 98u

Siarka :
98u - 100 %
32u - x
98x - 3200/: 98
x - 32.65%

39.02% - 32.65% =6.37 %